2020
DOI: 10.3892/ol.2020.11316
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatics analysis of the association between apolipoprotein E expression and patient prognosis in papillary thyroid carcinoma

Abstract: The prognosis of most patients with papillary thyroid carcinoma (PTC) is excellent despite some cases of tumor progression or relapse. The present study was designed to reveal possible prognostic risk indicators for PTC. Differentially expressed genes (DEGs) extracted from 4 Gene Expression Omnibus (GEO) cohorts were subjected to functional enrichment analyses by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genome (KEGG) pathway analysis. A dataset from The Cancer Genome Atlas (TCGA) was obtained to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
6
1
Order By: Relevance
“…ApoE is related to overall survival and disease-free survival significantly. Low expression of ApoE is also associated with the advanced TNM stage, which indicates that ApoE can act as a biomarker to predict PTC progression and prognosis (Jiang et al, 2020). In addition, liver X receptor β (LXRβ) is overexpressed in PTC and induce the expression of its target genes including APOC1, APOC2 and APOE, which may activate lipid metabolism and protein synthesis, thus facilitating cancer cell proliferation.…”
Section: Thyroid Cancermentioning
confidence: 99%
“…ApoE is related to overall survival and disease-free survival significantly. Low expression of ApoE is also associated with the advanced TNM stage, which indicates that ApoE can act as a biomarker to predict PTC progression and prognosis (Jiang et al, 2020). In addition, liver X receptor β (LXRβ) is overexpressed in PTC and induce the expression of its target genes including APOC1, APOC2 and APOE, which may activate lipid metabolism and protein synthesis, thus facilitating cancer cell proliferation.…”
Section: Thyroid Cancermentioning
confidence: 99%
“…In addition to this finding, data showed that decreased APOE expression in PTC is associated with a statically significant decreased overall survival and found no correlation with disease-free survival [188]. This finding conflicts with other papers that found a statistically significant correlation between APOE and disease-free survival in PTC patients [189,192,194]. Further investigations concluded that mRNA levels of APOE were positively associated with the TNM staging of PTC [189,194].…”
Section: Apolipoproteins In Thyroid Cancermentioning
confidence: 56%
“…A study utilizing the TCGA and GEO databases for analysis of neoplastic thyroid tissue identified 134 differentially expressed genes (DEGs) with upregulation and 106 DEGs with downregulation. The analysis revealed that these DEGs were enriched in thyroid hormone synthesis and metabolic pathways (11). Our findings on differentially expressed genes in thyroid cancer are consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%